On the anatomy of vertebrates, Volume 2, Birds and mammals - Owen, Richard 1804-1892 (Cambridge library collection. Zoology, 2011)
Richard Owen F.R.S. (1804–92) was a controversial and influential palaeontologist and anatomist. Owen studied medicine at the University of Edinburgh and at London's St Bartholomew's Hospital. He grew interested in anatomical research, and after qualifying he became assistant conservator in the museum of the Royal College of Surgeons, and then superintendent of natural history in the British Museum. He quickly became an authority on comparative anatomy and palaeontology, coining the term 'dinosaur' and founding the Natural History Museum. He was also a fierce critic of Darwin's theory of evolution by natural selection, and engaged in a long and bitter argument with Darwin's 'Bulldog', Thomas Huxley. Published in 1866, this is the second book in a highly illustrated three-volume set that comprises a thorough overview of vertebrate anatomy. This volume focuses on the anatomy of birds, and includes the first part of the analysis of mammalian anatomy